Penggunaan CSS-Mortar Busa Sebagai Alternatif Pemilihan Tipe Konstruksi Jalan Layang terhadap Biaya Konstruksi - Hinawan Teguh Santoso (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
The elevated road construction which is originally intended to overcome congestion at the intersection of the highway/train, actually sometimes worsen the congestion that exists during the construction period. Therefore, a new construction method and technology is needed to minimize the congestion and provide a short construction period. CSS-Mortar Foam is a new technology introduced by the Research Center of the Ministry of PUPR (Pusjatan) in 2016 which has been applied to the construction of the Antapani flyover in Bandung. A study is needed to compare the construction cost of this technology with the technology of the overpass structure which is commonly used, namely PCI-Girder. Data collection process in this study are planning and DED data, inventory of work items and volumes, and the unit price. The next step is the construction-costs calculation process of the proposed alternative-construction types. The calculation of construction costs was carried out using the Work Unit Price Analysis (AHSP) which is developed by the Directorate General of Highways based on the third revision of 2010 General Specifications. The results showed that the alternative CSS-Mortar Foam construction types was able to reduce the construction costs of flyovers by 44.7% compared to the PCI-Girder construction type. Thus, CSS-Mortar Foam construction can be used as a more efficient alternative for flyovers/bridges construction.